Приближенный расчет активного сопротивления и температуры канала импульсной электрической дуги в сильноточной разрядной цепи мощного высоковольтного емкостного накопителя энергии - Баранов, М.И.; Рудаков, С.В. (Електротехніка і електромеханіка, 2017)
Приведены результаты расчетной оценки эквивалентного активного сопротивления Rce канала импульсного дугового электрического разряда в воздушной двухэлектродной системе (ДЭС) сильноточной разрядной цепи мощного высоковольтного емкостного накопителя энергии (ЕНЭ), используемого при моделировании в лабораторных условиях длительной С- компоненты тока искусственной молнии. Рекомендовано расчетное соотношение для оценки максимальной электронной температуры Tme в низкотемпературной плазме канала импульсной электрической дуги в исследуемой воздушной ДЭС. Выполнена практическая апробация полученных соотношений для Rce и Tme применительно к воздушной ДЭС сильноточной разрядной цепи действующего мощного высоковольтного ЕНЭ генератора ГИТ-С, предназначенного для проведения испытаний технических объектов на электротермическую стойкость к воздействию длительной С- компоненты тока искусственной молнии с амплитудно-временными параметрами, соответствующими нормативным документам США SAE ARP 5412: 2013 и SAE ARP 5416: 2013. Приведені результати розрахункової оцінки еквівалентного активного опору Rce каналу імпульсного дугового електричного розряду в повітряній двоелектродній системі (ДЕС) сильноточного розрядного кола потужного високовольтного ємнісного накопичувача енергії (ЕНЕ), використовуваного при моделюванні в лабораторних умовах тривалої С- компоненти струму штучної блискавки. Рекомендовано розрахункове співвідношення для оцінки максимальної електронної температури Tme в низькотемпературній плазмі каналу імпульсної електричної дуги в досліджуваній повітряній ДЕС. Виконана практична апробація отриманих співвідношень для Rce і Tme стосовно повітряної ДЕС сильноточного розрядного кола потужного високовольтного ЕНЕ генератора ГИТ-С, що діє, призначеного для проведення випробувань технічних об'єктів на електротермічну стійкість до дії тривалої С- компоненти струму штучної блискавки з амплітудно-часовими параметрами, що відповідають нормативним документам США SAE ARP 5412: 2013 і SAE ARP 5416: 2013. Purpose. To obtain calculation correlations for active resistance Rce and maximal temperature Tme of plasma channel of pulse electric arc in the air double-electrode system (DES) with metal (graphite) electrodes, and also practical approbation of the obtained correlations for Rce and Tme in the conditions of high-voltage laboratory on the powerful capacity energy storage (CES) of electric setting, intended for reproducing on the electric loading of protracted C- component of current of artificial lightning with the USA rationed on normative documents by amplitude-temporal parameters (ATP). Methodology. Electrophysics bases of high-voltage impulse technique, scientific and technical bases of development and creation of high-voltage high-current impulse electrical equipment, including powerful CES, and also measuring methods in discharge circuits of powerful high-voltage CES of pulse currents of millisecond temporal range. Results. On the basis of engineering approach the new results of approximate calculation of values of Rce and Tme are resulted in the plasma channel of pulse electric arc discharge in air DES of atmospheric pressure with metallic (graphite) electrodes. Practical approbation of results of calculation of values of Rce and Tme is executed as it applies to air DES, to connected in a discharge circuit of powerful high-voltage CES with protracted C- of component current of artificial lightning, characterized rationed ATP. It is shown that calculation of numeral value Rce approximately in 100 times exceeds the proper value of active resistance for the plasma channel of impulsive spark of electric discharge in air DES other things being equal, and a calculation of numeral value Tme well corresponds with the known thermodynamics information for classic electric arc in air DES of atmospheric pressure with graphite electrodes. Originality. New engineering approach is developed for the approximate calculation of values of Rce and Tme in electron-ion plasma of channel of pulse electric arc, arising in air DES of high-current discharge circuit of powerful high-voltage CES of proof-of-concept of electric setting of the technological setting. A formula is first obtained for the approximate calculation of equivalent active resistance of Rce of channel of pulse electric arc in air DES, remaining unchanging in the process of highcurrent discharge on RL- load of indicated CES. Practical value. Drawing on the got calculation results for the values of Rce and Tme in high-voltage impulse technique provides the rational choice of own electric parameters and construction elements of basic devices of powerful high-voltage CES of technological of electric setting, and also account of influence of electrical engineering descriptions of air DES on electromagnetic processes, taking place in the high-current discharge circuit of indicated CES with protracted C- of component current of artificial lightning.